ANALISIS PENGARUH CAR, NPL, BOPO, NIM, DAN LDR TERHADAP ROA PT. BANK SULSELBAR PERIODE 2001-2010 - Sohilauw, Muhammad Irfai (Jurnal Ilmiah Ecosystem, 2016)
This research aims to analyze the effect of Capital Adequacy Ratio (CAR), the NonPerforming Loan (NPL), Net Interest Margin, BOPO (NIM) and Loan to Deposit Ratio(LDR) towards Return On Assets (ROA) of PT. Bank Sulselbar the period 2001-2010. Theresults showed that the variable CAR and NIM positive effect against ROA, while theNPL, NIM and influential BOPO negative against ROA. Then the five variablessimultaneously affect a variable is bound (ROA).Strategies for keeping consistency CAR: (1) maintaining credit quality, (2) purchaseof shares, (3) deposit additional capital for the company's operations, (4) Perform rightissue, (5) conversion of profits/retained earnings into a capital and delaying the Divisionof bonuses and dividends. How to lose as well as maintain the NPL: (1) did the principleof prudence in every channeling credit, (2) more intensive charging to the debtor, (3) adebt restructuring Offer, (4) the Himura Kenshin Performs warranty and sell thecollateral, (5) withdrawals capital reserves of banks, (6) improving the quality of creditanalysis. To maintain quality BOPO, then operational efficiency in absolutely should bekept. To improve the NIM: (1) to reproduce the distribution of productive sector credit,(2) Provide high interest rates on consumer credit as well as being at high risk, (3)maintain the credit quality. And Lastly, to maintain the stability of LDR: (1) expansion ofcredit, (2) increase the value of third party funds, (3) maintain the composition betweenchanneling credits and gathering together the funds (were in the range of 80 – 100%)